Uterine Fibroids: Pathogenesis and Interactions with Endometrium and Endomyometrial Junction. (12th September 2013) - Ciavattini, Andrea; Di Giuseppe, Jacopo; Stortoni, Piergiorgio; Montik, Nina; Giannubilo, Stefano R.; Litta, Pietro; Islam, Md. Soriful; Tranquilli, Andrea L.; Reis, Fernando M.; Ciarmela, Pasquapina
Abstract : Uterine leiomyomas (fibroids or myomas) are benign tumors of uterus and clinically apparent in a large part of reproductive aged women. Clinically, they present with a variety of symptoms: excessive menstrual bleeding, dysmenorrhoea and intermenstrual bleeding, chronic pelvic pain, and pressure symptoms such as a sensation of bloatedness, increased urinary frequency, and bowel disturbance. In addition, they may compromise reproductive functions, possibly contributing to subfertility, early pregnancy loss, and later pregnancy complications. Despite the prevalence of this condition, myoma research is underfunded compared to other nonmalignant diseases. To date, several pathogenetic factors such as genetics, microRNA, steroids, growth factors, cytokines, chemokines, and extracellular matrix components have been implicated in the development and growth of leiomyoma. This paper summarizes the available literature regarding the ultimate relative knowledge on pathogenesis of uterine fibroids and their interactions with endometrium and subendometrial myometrium.